2016
DOI: 10.1002/bdm.2000
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Delay Discounting and Risk‐Related Behaviors, Traits, Attitudes, and Outcomes

Abstract: Delay discounting—preference for immediate, smaller rewards over distal, larger rewards—has been argued to be part of the “generality of deviance”, which describes the co‐occurrence of various forms of impulsive and risky behaviors among individuals. Some studies have linked laboratory‐measured delay discounting to behaviors, traits, attitudes, and outcomes associated with risk, but these associations have been inconsistent. Furthermore, many of these studies have been conducted with exclusively undergraduate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 79 publications
(108 reference statements)
1
31
1
Order By: Relevance
“…One form of impulsive decision‐making is delay discounting, or the tendency to seek immediate, smaller rewards instead of larger rewards that are delayed in time. Not surprisingly, previous research has found that offenders exhibit problems delaying gratification on delay discounting tasks (Åkerlund, Golsteyn, Grönqvist, & Lindahl, ; Carroll et al, ; Lee et al, ; Mishra & Lalumière, ). In addition, steeper devaluing of delayed rewards significantly predicts future engagement in criminal behaviour, even after controlling for several other known risk factors (Lee et al, ).…”
Section: Introductionmentioning
confidence: 95%
“…One form of impulsive decision‐making is delay discounting, or the tendency to seek immediate, smaller rewards instead of larger rewards that are delayed in time. Not surprisingly, previous research has found that offenders exhibit problems delaying gratification on delay discounting tasks (Åkerlund, Golsteyn, Grönqvist, & Lindahl, ; Carroll et al, ; Lee et al, ; Mishra & Lalumière, ). In addition, steeper devaluing of delayed rewards significantly predicts future engagement in criminal behaviour, even after controlling for several other known risk factors (Lee et al, ).…”
Section: Introductionmentioning
confidence: 95%
“…For example, selecting an immediate £5 payoff, over a £10 reward given the following day. As with behavioural disinhibition, delay discounting has found to be associated with increased risk-taking (Courtney et al, 2012;Mishra & Lalumière, 2017), and seems to be elevated in heavy and harmful drinkers (Moody, Tegge, & Bickel, 2017). As such, both constructs of impulsivity are seemingly related to both risk-taking and alcohol use.…”
Section: Risky To Whiskymentioning
confidence: 99%
“…Contrary to previous findings, delay discounting was not associated with personal relative deprivation (e.g., Callan et al ., ; Tabri, Shead & Wohl, ), smoking cigarettes (e.g., Bickel, Odum & Madden, ; Reimers et al ., ), or procrastination (Schouwenburg & Groenewoud, ). Additionally, delay discounting was only sometimes related to arrests (e.g., Mishra & Lalumière, ) and frequency of drinking alcohol. However, these differences may be due to the measurement differences in the present study; that is, we assessed frequency of alcohol intake instead of alcoholism (e.g., Petry, ).…”
Section: Discussionmentioning
confidence: 99%
“…We adapted a single‐shot discounting measure (Mishra & Lalumière, , ; Reimers et al ., ) to an online format after piloting various payment structures (see Table ). Participants were presented with the following question: “Would you prefer: $0.15 today or $0.23 in 21 days?” Those who chose the immediate option (i.e., those who discounted the future) were coded as 1 and those who chose the delayed option were coded as −1, such that positive scores indicated greater discounting.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation